Fixed-dose ivermectin for Mass Drug Administration: Is it time to leave the dose pole behind? Insights from an Individual Participant Data Meta-Analysis - Echazu, Adriana; Bonanno, Daniela; Fleitas, Pedro Emanuel; Jacobson, Julie; Matamoros, Gabriela; Mwandawiro, Charles; Enbiale, Wendemagegn; de Jesus, Áuria; Brooks, Alan; Krolewiecki, Alejandro Javier (PLOS Neglected Tropical Diseases, 2025)
Author summary Ivermectin is an essential drug with proven safety and effectiveness against several parasitic infections. It plays a key role in Mass Drug Administration (MDA) programs targeting prevalent Neglected Tropical Diseases. Currently, ivermectin dosing is based on weight or height, which can be difficult to measure in the field during MDA campaigns and adds complexity and workload for health workers. These methods also carry a risk of underdosing. In this study, we analyzed data from more than 700,000 participants across 53 countries to explore whether a fixed-dose approach could simplify MDA implementation while maintaining doses within the therapeutic range. We found that fixed-dose regimens provide more accurate treatment for a larger proportion of individuals, reduce the likelihood of underdosing, and only occasionally result in doses above the recommended levels, typically by small margins and in a limited proportion of participants. This simplified approach could ease treatment delivery in community settings and improve coverage and operational efficiency. Our findings provide practical evidence to inform policy discussions on how to streamline and strengthen ivermectin-based MDA programs.